4-Azidobenzyl ferrocenylcarbamate as an anticancer prodrug activated under reductive conditions - Kinski, Elisa; Marzenell, Paul; Hofer, Walter; Hagen, Helen; Raskatov, Jevgenij A.; Knaup, Karl; Zolnhofer, Eva; Meyer, Karsten; Mokhir, Andriy (Journal of Inorganic Biochemistry, 2016)
Aminoferrocene-based prodrugs are activated in the presence of cancer-specific amounts of reactive oxygen species, e.g. H2O2, with the formation of products of two types: Fe-containing complexes, which catalyze generation of HO and O2-, and quinone methides, which alkylate glutathione and inhibit the antioxidative system of the cell. Both processes act synergistically by increasing the oxidative stress in cancer cells thereby leading to their death. However, in the activation step including the cleavage of a B-C bond one molecule of H2O2 is consumed that counteracts the desired effect of the products released from aminoferrocenes. We replaced an H2O2-sensitive trigger in original prodrugs with an azide group. This trigger is slowly reduced in the presence of glutathione with the formation of an unstable arylamine intermediate, which decomposes with the release of iron ions and iminoquinone methides. These products induce strong oxidative stress in cells as we confirmed using 2′,7′-dichlorodihydrofluorescin diacetate reagent in combination with flow cytometry. In this case the activation process does not consume H2O2. Correspondingly, we observed that the azide-containing prodrug is substantially more toxic towards human promyelocytic leukemia cell line HL-60 (IC50 = 27 ± 4 μM) than its H2O2-responsive analogue (IC50 > 50 μM).
CRIS-Team Scopus Importer:2020-09-14
Keywords: Azide; Cancer; Ferrocene; Prodrug; Reduction

Tuning the structure of aminoferrocene-based anticancer prodrugs to prevent their aggregation in aqueous solution - Daum, Steffen; Babiy, Svetlana; Konovalova, Helen; Hofer, Walter; Shtemenko, Alexander; Shtemenko, Natalia; Janko, Christina; Alexiou, Christoph; Mokhir, Andriy (Journal of Inorganic Biochemistry, 2018)
Aminoferrocene-based prodrugs are activated in cancer cells by reactive oxygen species (ROS). They were shown to exhibit high cytotoxicity towards a variety of cancer cell lines and primary cancer cells, but remain not toxic towards non-malignant cells. However, these prodrugs have rather high lipophilicity leading to relatively low water solubility. In particular, an n-octanol/water partition coefficient for the best aminoferrocene-based pro drug (2) was found to be 4.51 +/- 0.03. Though the approaches for decreasing lipophilicity are straightforward and include the addition of polar residues to the drug structure, these modifications also lead to dramatic decrease of cell permeability and, correspondingly, lower the activity of the drug. Therefore, a delicate balance of polar and unpolar groups should be found to reduce lipophilicity without compromising the useful drug properties. In this study we optimized an N-alkyl substituent, which is a key element responsible for the stabilization of the aminoferrocene drug released in cancer cells from prodrug 2. We found that an N-propargyl residue is an optimal replacement for the N-benzyl fragment. In particular, such a substitution (prodrug 7a) leads to reduction of prodrug lipophilicity down to logP = 3.78 +/- 0.05, improvement of its water solubility, decrease of its propensity towards aggregation and dramatic increase of its ROS-generating properties. Finally, we demonstrated that the optimized prodrug strongly suppresses growth of Guerin's carcinoma (T8) in vivo at the dose of 30 mg/kg.
EVALuna2:213359